2013
DOI: 10.1002/j.1556-6676.2013.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Multicultural Competence Among School Counselors: Multicultural Training, Racial/Ethnic Identity, and Color‐Blind Racial Attitudes

Abstract: This study tested a model that links race/ethnicity, multicultural training, racial/ethnic identity (REI), color‐blind racial attitudes (CoBRA), and multicultural counseling competence (MCC) among school counselors. The author examined whether multicultural training significantly moderated the association between race/ethnicity and MCC. School counselors’ REI was found to mediate this moderated association. A 3‐way interaction among race/ethnicity, training, and CoBRA revealed that White and racial/ethnic mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
108
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 45 publications
14
108
1
Order By: Relevance
“…Findings from this study are consistent with those of previous empirical literature that suggest that counselors of color score significantly higher than White counselors across a number of multicultural competence subscales that measure counselor awareness, knowledge, and skills with culturally diverse clients (Chao, 2006;Chao et al, 2011;Hill et al, 2013;Ponterotto et al, 1996;Pope-Davis & Ottavi, 1994;Vinson & Neimeyer, 2000, 2003. Furthermore, findings from this study are consistent with Sheu and Lent's (2007) research that supports differences between White trainees and trainees of color on some dimensions of multicultural CSE.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings from this study are consistent with those of previous empirical literature that suggest that counselors of color score significantly higher than White counselors across a number of multicultural competence subscales that measure counselor awareness, knowledge, and skills with culturally diverse clients (Chao, 2006;Chao et al, 2011;Hill et al, 2013;Ponterotto et al, 1996;Pope-Davis & Ottavi, 1994;Vinson & Neimeyer, 2000, 2003. Furthermore, findings from this study are consistent with Sheu and Lent's (2007) research that supports differences between White trainees and trainees of color on some dimensions of multicultural CSE.…”
Section: Discussionsupporting
confidence: 92%
“…A majority of studies that have assessed multicultural competence indicated that counselors of color scored significantly higher than White counselors across a number of subscales that measure counselor awareness, knowledge, and skills in clinical work with diverse clients (Chao, 2006;Chao et al, 2011;Hill et al, 2013;Ponterotto et al, 1996;Pope-Davis & Ottavi, 1994;Vinson & Neimeyer, 2000, 2003. For example, in their initial scale development of the Multicultural Awareness Scale, Ponterotto and colleagues (1996) found that when they combined trainees of color into one group, trainees of color scored significantly higher than White trainees on the Knowledge and Skills subscales.…”
Section: Trainee Race and Multicultural Competencementioning
confidence: 98%
See 1 more Smart Citation
“…Taken together, these studies indicate that multicultural training enhances the knowledge-base for counselors-in-training, and may subsequently increase the level of multicultural effectiveness for counselors in the field. Chao (2013) found that multicultural training enhances school counselors' multicultural counseling competence (MCC) by assisting counselors to become more aware of their own racial/ethnic backgrounds while advancing their knowledge of color-blind racial attitudes (CoBRA). This study stressed the importance of a 3-way interaction among race/ethnicity, training, and CoBRA in order to increase their MCC.…”
Section: Cognitive-knowledge Domainmentioning
confidence: 99%
“…As there is an established link within the school counseling literature between exposure to specific topics and experiences in counselor training and subsequent attitudes and behaviors in practice (Chao, 2013;Scarborough & Luke, 2008), there are several potential implications for counselor educators and supervisors. First, school counselor education programs may benefit from an internal audit to assess when and how the curricula addresses professional identity and peer membership.…”
Section: School Counselor Preparationmentioning
confidence: 99%